2022
DOI: 10.1055/s-0042-1742718
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GFAP Antibody-Associated Hypertrophic Pachymeningitis

Abstract: Background Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is an inflammatory central nervous system (CNS) disorder that usually presents as steroid responsive encephalitis, meningitis, myelitis, or meningoencephalomyelitis. Hypertrophic pachymeningitis (HP) is an uncommon disorder that causes a localized or diffuse thickening of the dura mater. Depending on the etiology, HP can be idiopathic or secondary to a wide variety of other diseases. There are no reports of autoimmune GFAP astrocytopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the patient described in this study, gadolinium contrast-enhanced brain MRI scans showed a heterogeneous thickening of the dura mater. Similarly, a recent report described a pediatric patient with hypertrophic pachymeningitis associated with GFAP-A, and the authors indicate that hypertrophic pachymeningitis may be one of the clinical phenotypes for GFAP-A [19], which is also corroborated by our findings.…”
Section: Discussionsupporting
confidence: 91%
“…In the patient described in this study, gadolinium contrast-enhanced brain MRI scans showed a heterogeneous thickening of the dura mater. Similarly, a recent report described a pediatric patient with hypertrophic pachymeningitis associated with GFAP-A, and the authors indicate that hypertrophic pachymeningitis may be one of the clinical phenotypes for GFAP-A [19], which is also corroborated by our findings.…”
Section: Discussionsupporting
confidence: 91%
“…24 Pediatric patients have been successfully treated with varying combinations of therapies, often including intravenous methylprednisolone and intravenous immune globulin, with variable inclusion of PLEX and/or long-term immunosuppressants. 210,13,14 Our experience demonstrates that pediatric patients may require combination acute treatment with intravenous methylprednisolone, intravenous immune globulin, and PLEX, as 4 of our 5 patients were not responsive to intravenous methylprednisolone and intravenous immune globulin alone, supporting consideration of early initiation of PLEX.…”
Section: Discussionmentioning
confidence: 68%
“…Although oncologic processes have been reported as a common potential trigger of GFAP astrocytopathy in adults, 7 among pediatric patients, a potential oncologic trigger has only rarely been identified. 6,9,10,13,14 This suggests that other factors may trigger GFAP autoimmunity in children. Infectious triggers have also been linked to GFAP astrocytopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2016 study by Flanagan et al found that 17 out of 38 patients with GFAP astrocytopathy had a typical linear perivascular radial gadolinium pattern enhancement, while 7 had normal imaging results [ 3 ]. Recently, some case reports have shown that, in addition to common site lesions, such as the subcortical white matter, basal ganglia, hypothalamus, brainstem, cerebellum, and spinal cord, GFAP astrocytopathy can also manifest as hypertrophic meningoencephalitis [ 5 ] or mild encephalitis with reversible splenial corpus callosum lesions [ 6 ]. This patient had no typical linear lesions, but the CSF GFAP antibodies were highly specific and sensitive and led to the diagnosis of GFAP astrocytopathy.…”
Section: Discussionmentioning
confidence: 99%